A Decision-Support Framework for Enhancing Industrial Chain Resilience through Green Finance: Evidence from China’s Sports Industry - Dangsheng Wang; Qiuying Li; Wenxiang Zhou; Laibing Lu (Decision Making: Applications in Management and Engineering, 2025)
To examine the decision-making implications of green finance (Gre) development mechanisms in China on the resilience of the sports industry chain (SICR), this study utilises a sample drawn from 24 provincial-level regions within the country. Initially, evaluation index systems for both Gre and SICR are established. Subsequently, the study investigates the complex linear and non-linear interactions between the development of green finance and SICR in China, providing a decision-support framework aimed at optimising the allocation of green financial resources and enhancing SICR. The findings indicate that: (1) advancements in the level of green financial development exert a significant positive influence on the resilience of SICR; (2) Gre affects SICR partially through the channel of sports industry innovation, which functions as a partial mediator, with this mediation pathway accounting for 23.8% of the total effect; (3) the impact of Gre on SICR is characterised by non-linear dynamics, whereby Gre can bolster SICR only when regional economic level, digital economy development, market maturity, and residents’ consumption capacity surpass specific threshold values.